Climate Risk Management in Agricultural Extension (CRMAE) Curriculum: Training of Trainers and Adaptation to the ATVET Program. - Grossi, Amanda; Dinku, Tufa; Hansen, James; Belay, Berhanu; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A six-day training of trainers (ToT) workshop on the Climate Risk Management in Agricultural Extension (CRMAE) curriculum and its adaptation to Ethiopia’s Agricultural Technical and Vocational Education and Training (ATVET) colleges was convened from May 29 to June 3, 2023, in Addis Ababa, Ethiopia by the Ministry of Labor and Skills (MoLS) and Ministry of Agriculture (MoA), in close collaboration with the International Research Institute for Climate and Society (IRI) of the Columbia Climate School and the International Livestock Research Institute (ILRI). The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 13 participants from Ethiopia’s federal ATVET colleges and representatives from the MoA and MoLS to capacitate them on the CRMAE curriculum as well as to develop a roadmap for its adaptation for a unit of competence within the ATVET curriculum. Beyond this, the MoLS and MoA committed to moving forward to adopt the curriculum as a cross-cutting course nationally with both federal and regional ATVET colleges, as well as to integrate it within other occupational standards and units of competence beyond the one originally identified for this workshop.